High Technology in Geothermal Fish Farming at Silfurstjarnan Ltd., NE-Iceland - Georgsson, Ludvik S. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1996)
Land-based fish farming in Iceland relies on good resources of freshwater and seawater with thermal energy to warm it up. In Oexarfjoerdur, NE-Iceland plentiful cold groundwater exists and geothermal manifestations are found at many locations. Seawater resources are, apart from the unstable sand shore, limited to a pillow lava formation close to the shore. During 1986-1990, Orkustofnun - the National Energy Authority of Iceland joined with local authorities in Oexarfjoerdur to study the potential of the area for fish farming. The project led to the forming of the company Silfurstjarnan Ltd., which built and presently runs a fish farm in Nupsmyri in Oexarfjoerdur